Pengaruh Religiusitas, Moral Pajak, dan Sistem Perpajakan terhadap Penggelapan Pajak - Adedyani Putri; Nuramalia Hasanah; Dwi Handarini (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This research was conducted to determine the effects of religiosity, taxpayer morale, and the tax system of online business actors on tax evasion. This research uses a quantitative method as a research method. The research data used is primary data, with research instruments in the form of questionnaires. The population used in this research was 252,953 MSMEs in the East Jakarta area, based on data from the Central Statistics Agency. The sample used in this research was 100 MSME actors. The data analysis method used was multiple linear analysis with the help of the SPSS version 22 program. Based on the results of the analysis conducted, it can be concluded that religiosity and the tax system have a significant effect on tax evasion, while tax morale has no effect on tax evasion.